PENGARUH PENERAPAN METODE AL HIWAR TERHADAP HASIL BELAJAR BAHASA ARAB PADA SISWA KELAS VII DI PONDOK PESANTREN FAJRUSSALAM - Muhamad Alim Nur; Santi Lisnawati (KOLONI, 2022)
Arabic learning methods and innovations will be a challenge for every Arabic teacher. Therefore, learning Arabic also demands the intelligence of every teacher to understand aspects related to learning outcomes. Namely by creating new techniques in learning Arabic so that students become more active, skilled, able to master and proficient in Arabic. This study aims to find out how the implementation of the Al Hiwar method in class VII Boarding school of Fajrussalam and to find out the improvement in learning Arabic in class VII Boarding school of Fajrussalam. The research method used in this study uses a quasi-experimental method, which is a form of research that has a control group, but cannot function fully to control external variables that affect the implementation of the research. The results of the study prove that there is an influence of the Al-Hiwar Method in the learning outcomes of Arabic. The study results describe the average value of students in the cognitive aspect with the results of the experimental class average score of 83.75. Meanwhile, the average value of the control class is 65.78. So that in carrying out learning Arabic subjects are expected to be able to use various learning methods that are adapted to the material being taught, so as to create a pleasant learning atmosphere which can ultimately improve student learning outcomes. Keywords: Arabic Learning, Al-Hiwar Method